Role of hippocampal neurogenesis in mnemonic segregation: implications for human mood disorders. (December 2013) - Perera, Tarique D.; Thirumangalakudi, Lakshmi; Glennon, Erin; Park, Sungshic; Insanally, Michele; Persky, Michael; Fonseka, Janaki; Dwork, Andrew J.; Sackeim, Harold A.; Coplan, Jeremy D.; Fenton, André A.
Abstract Objectives. Although hippocampal neurogenesis has been implicated in mood disorders, the precise role new neurons play in mood regulation is not fully elucidated. Here we examine whether neurogenesis improves mood by facilitating segregation of novel experiences that conflict with older maladaptive memories. Methods. Study 1: Four groups (N = 9 each) of adult male rats (exposed to stress or control conditions plus antidepressant or placebo) underwent active training on the place-avoidance task (PAT) on week 0; tested on recalling the "Initial PAT" on weeks 4 and 8; learning a subtly "Altered PAT" on week 8; and euthanazed on week 9. Study-2: Two groups (N = 12 each) rats tested either on the Initial-PAT or Altered-PAT 3 days post-training and immediately euthanized. Results. Stressed subjects treated with placebo were slower in learning the week 8 Altered Task and had lower neurogenesis rates than non-stressed animals and Stressed subjects given drug (Study 1). Synaptic activation of mature hippocampal neurons inversely correlated with Altered-PAT performance and with neurogenesis rates (Study 2). Conclusions. Increasing neurogenesis enhances acquisition of novel experiences possibly by suppressing activation of mature hippocampal neurons that mediate established, conflicting memories. Therefore, antidepressants may improve mood by stimulating new hippocampal neurogenesis that facilitate detection of positive experiences while suppressing interference from recurring depressogenic thought patterns.